2020
DOI: 10.3897/neotropical.15.e51738
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution and conservation of seasonal killifishes (Cyprinodontiformes, Rivulidae) from the Mid-Northeastern Caatinga ecoregion, northeastern Brazil

Abstract: The Rivulidae fish family, which includes Neotropical seasonal killifishes, is one of the most diverse taxonomic groups in the aquatic systems of Caatinga in Brazil. Cynolebias and Hypsolebias genera, with 20 and 35 endemic species, respectively, concentrate the greatest diversity of rivulid species in the semiarid. Sixty-eight years after the first records of annual killifishes in the Mid-Northeastern Caatinga ecoregion (MNCE), only four valid species have been sampled in this area. Here we combined bibliogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The two seasonal killifishes species sampled, C. microphthalmus and H. antenori (in the sites 3, 7, 8 and 9), have been previously recorded by Abrantes et al (2020), which also pointed out the anthropogenic pressures affecting the temporary pools in the region. Abrantes et al (2020) suggested an expansion of the current area of the FFNP as the main protection measure for the conservation of these two species. An alternative approach for the conservation of C. microphthalmus would be the introduction of some specimens in the FFNP sites 4 and 5 (temporary pools currently without fish).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The two seasonal killifishes species sampled, C. microphthalmus and H. antenori (in the sites 3, 7, 8 and 9), have been previously recorded by Abrantes et al (2020), which also pointed out the anthropogenic pressures affecting the temporary pools in the region. Abrantes et al (2020) suggested an expansion of the current area of the FFNP as the main protection measure for the conservation of these two species. An alternative approach for the conservation of C. microphthalmus would be the introduction of some specimens in the FFNP sites 4 and 5 (temporary pools currently without fish).…”
Section: Discussionmentioning
confidence: 66%
“…During the last century, the ichthyofauna of the RN has been investigated using different approaches, such as inventories and ecological studies (Starks, 1913;Nascimento et al, 2014;Paiva et al, 2014;Costa et al, 2017;Medeiros et al, 2019). However, only two studies recorded fishes in caves (Ferreira et al, 2010;Abrantes et al, 2020). In order to identify potential temporary refuges for fishes in the dry season or even potentially troglobitic fishes, we surveyed the ichthyofauna of surface and subterranean springs in karstic landscapes of the Jandaíra Formation in the Caatinga's drainages.…”
mentioning
confidence: 99%